Comprehensive analysis of the air quality impacts of switching a marine vessel from diesel fuel to natural gas. (November 2020) - Peng, Weihan; Yang, Jiacheng; Corbin, Joel; Trivanovic, Una; Lobo, Prem; Kirchen, Patrick; Rogak, Steven; Gagné, Stéphanie; Miller, J. Wayne; Cocker, David
Abstract: New environmental regulations are mandating cleaner fuels and lower emissions from all maritime operations. Natural gas (NG) is a fuel that enables mariners to meet regulations; however, emissions data from maritime operations with natural gas is limited. We measured emissions of criteria, toxic and greenhouse pollutants from a dual-fuel marine engine running either on diesel fuel or NG as well as engine activity and analyzed the impacts on pollutants, health, and climate change. Results showed that particulate matter (PM), black carbon (BC), nitric oxides (NOx ), and carbon dioxide (CO2 ) were reduced by about 93%, 97%, 92%, and 18%, respectively when switching from diesel to NG. Reductions of this magnitude provide a valuable tool for the many port communities struggling with meeting air quality standards. While these pollutants were reduced, formaldehyde (HCHO), carbon monoxide (CO) and methane (CH4 ) increased several-fold. A health risk assessment of exhaust plume focused on when the vessel was stationary, and at-berth showed the diesel plume increased long-term health risk and the NG plume increased short-term health risk. An analysis of greenhouse gases (GHGs) and BC was performed and revealed that, on a hundred year basis, the whole fuel cycle global warming potential (GWP) per kWh including well-to-tank and exhaust was 50% to few times higher than that of diesel at lower engine loads, but that it was similar at 75% load and lower at higher loads. Mitigation strategies for further reducing pollutants from NG exhaust are discussed and showed potential for reducing short-term health risks and climate impacts. Graphical abstract: Image 1 Highlights: Compared exhaust emissions from a marine vessel powered by natural gas and diesel. Natural gas reduced NOx and PM2.5 emissions by >90%; increased formaldehyde by 600%. Natural gas reduced long-term health risk but increased short-term health risk. Natural gas increased global warming potential (GWP) for engine loads <75%. Mitigation methods evaluated to reduce GWP and health risks of natural gas.